Technology-Integrated Catechism Curriculum: A Systematic Literature Review on Strengthening Youth Faith and Preventing Juvenile Delinquency - Rependi Sianturi; Darul Ilmi (JTP - Jurnal Teknologi Pendidikan, 2026)
This study addresses the increasing problem of juvenile delinquency among Indonesian youth, including church adolescents, by examining the need for a more relevant and transformative catechism curriculum. The research employs a qualitative systematic literature review of peer-reviewed articles on catechesis, Christian religious education, youth faith formation, and juvenile delinquency. The inclusion criteria covered publications from 2021 to 2025 in English and Indonesian; however, all selected studies were published between 2023 and 2025 due to their stronger relevance and methodological suitability. The findings indicate that effective catechism curricula must adopt a holistic, contextual, and participatory approach integrating theological perspectives, adolescent developmental psychology, and character education. In addition, this study highlights that the integration of educational technology—such as digital media, e-learning platforms, and interactive applications—is a critical component in enhancing engagement, accessibility, and learning effectiveness among digital-native youth. The proposed curriculum framework emphasizes contextual theological content, student-centered learning strategies, experiential spiritual practices, and sustainable mentoring supported by collaboration among church, family, and educational institutions. This study contributes theoretically by integrating faith formation and educational technology within a unified framework and practically by offering a technology-integrated catechism curriculum model to strengthen youth faith and moral resilience in addressing juvenile delinquency.